2018
DOI: 10.1111/jcmm.13820
|View full text |Cite
|
Sign up to set email alerts
|

25‐Hydroxycholesterol protects against acute lung injury via targeting MD‐2

Abstract: Acute lung injury (ALI) is mainly caused by uncontrolled inflammatory response, and it remains without effective therapeutic options. 25‐hydroxycholesterol (25HC) has been reported to be a potent regulator of inflammation. The aim of this study was to investigate the effects of 25HC on lipopolysaccharide (LPS)‐induced ALI. C57BL/6 mice were pretreated with 25HC intraperitoneally before intratracheal exposure to LPS. Our results showed that 25HC pretreatment improved survival rate, attenuated the pathological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…[13][14][15][16] In addition, 25-HC significantly reduced LPSinduced inflammatory response through interaction with myeloid differentiation protein 2. [17] In this study, we have undertaken further investigation on the pathophysiological role of 25-HC in X-ALD and revealed significant reduction of VLCFA (C26:0) by exogenous addition of 25-HC.…”
Section: Exogenous Addition Of 25-hydroxycholesterol Reduces Level Ofmentioning
confidence: 91%
See 1 more Smart Citation
“…[13][14][15][16] In addition, 25-HC significantly reduced LPSinduced inflammatory response through interaction with myeloid differentiation protein 2. [17] In this study, we have undertaken further investigation on the pathophysiological role of 25-HC in X-ALD and revealed significant reduction of VLCFA (C26:0) by exogenous addition of 25-HC.…”
Section: Exogenous Addition Of 25-hydroxycholesterol Reduces Level Ofmentioning
confidence: 91%
“…It also has been demonstrated that 25‐HC acts as an intrinsic lipid effector of the interferon antiviral response and suppresses viral infection for a broad range of viruses including zika virus . In addition, 25‐HC significantly reduced LPS‐induced inflammatory response through interaction with myeloid differentiation protein 2 …”
Section: Figurementioning
confidence: 99%
“…Knockdown of pCH25H enhances E protein-mediated inflammatory responses. In addition to its antiviral activity, recent studies have suggested that 25HC, the metabolic product of CH25H, also regulates inflammatory cytokine production in vitro and in vivo (40,41). Coincidentally, PRRSV E protein has been demonstrated to induce inflammatory cytokine production (42,43), which is potentially associated with the PRRSV-induced inflammatory cytokine storm that occurs in late stages of virus infection.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we further investigated the potential relationship between pCH25H and PRRSV E protein-mediated inflammatory responses. Considering that conflicting results have been reported for the effects of 25HC on inflammatory responses (40,41,44,45), possible reasons for these discrepancies may be that different cell types and/or different concentrations of 25HC were used in the studies. Thus, we first evaluated the inflammatory cytokine expression of 3D4/21 cells after treatment with different concentrations of 25HC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation